A necessary condition for the tightness of odd-dimensional combinatorial manifolds. (January 2016) - Spreer, Jonathan
Abstract: We present a necessary condition for ( ℓ − 1 ) -connected combinatorial ( 2 ℓ + 1 ) -manifolds to be tight. As a corollary, we show that there is no tight combinatorial three-manifold with first Betti number at most two other than the boundary of the four-simplex and the nine-vertex triangulation of the three-dimensional Klein bottle.